1996
DOI: 10.1104/pp.111.1.313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COR6.6 and COR15am Polypeptides Encoded by COR (Cold-Regulated) Genes of Arabidopsis thaliana on the Freeze-Induced Fusion and Leakage of Liposomes

Abstract: Severa1 cold-regulated (COR) polypeptides, which have little or no amino acid sequence identity with known proteins, are synthesized during cold acclimation of Arabidopsis fhaliana. However, the function of the polypeptides has yet to be elucidated. l h e objective of this study was to determine if COR6.6 and COR15am influence the incidence of either freeze-induced fusion or freeze-induced leakage of small unilamellar vesicles (SUVs) composed of either a single species of phosphatidylcholine (either 1 -palmito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 30 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…This incubation produced no changes in the CD spectrum of rGmD-19 (data not shown), suggesting that the protein is unable to interact with zwitterionic phospholipid membranes. This result is in agreement with previous studies showing the lack of a specific phospholipid-protein interaction of other coldinduced proteins (Uemura et al, 1996;Webb et al, 1996). Although these results cannot discount the possibility that this group 1 LEA protein may interact with and be influenced by interaction with membrane lipids in vivo, we suggest that such interactions are unlikely given the extremely hydrophilic nature of this protein.…”
Section: Table I Secondary Structure Fractions Of Rgmd-19supporting
confidence: 81%
“…This incubation produced no changes in the CD spectrum of rGmD-19 (data not shown), suggesting that the protein is unable to interact with zwitterionic phospholipid membranes. This result is in agreement with previous studies showing the lack of a specific phospholipid-protein interaction of other coldinduced proteins (Uemura et al, 1996;Webb et al, 1996). Although these results cannot discount the possibility that this group 1 LEA protein may interact with and be influenced by interaction with membrane lipids in vivo, we suggest that such interactions are unlikely given the extremely hydrophilic nature of this protein.…”
Section: Table I Secondary Structure Fractions Of Rgmd-19supporting
confidence: 81%
“…For instance, Lin and Thomashow (35) reported that the unprocessed COR15a polypeptide is effective in decreasing the incidence of freeze-induced inactivation of lactate dehydrogenase in vitro, but subsequent studies indicate that the cryoprotective effect of COR15am on lactate dehydrogenase is no greater than that of bovine serum albumin (S.J.G., unpublished data). Uemura et al (36) have found that COR15am decreases the incidence of freeze-induced fusion of liposomes frozen in vitro. However, this effect only occurs under unusual conditions-when the liposomes are frozen in dilute buffer in the absence of any solutes.…”
Section: Discussionmentioning
confidence: 99%
“…CAregulated genes have been identified from numerous plant species including winter wheat (4 -6), barley (7,8), alfalfa (9 -11), and Arabidopsis (12)(13)(14). Positive correlations of coldinduced genes and freezing tolerance have been observed (10,15), and functions related to cold acclimation have been suggested for several genes (16,17).…”
mentioning
confidence: 99%